Skeletal Muscle Homeostasis in Duchenne Muscular Dystrophy: Modulating Autophagy as a Promising Therapeutic Strategy - De Palma, Clara; Perrotta, Cristiana; Pellegrino, Paolo; Clementi, Emilio; Cervia, Davide (Frontiers in Aging Neuroscience, 2014)
Muscular dystrophies are a group of genetic and heterogeneous neuromuscular disorders characterized by the primary wasting of skeletal muscle. In Duchenne muscular dystrophy (DMD), the most severe form of these diseases, the mutations in the dystrophin gene lead to muscle weakness and wasting, exhaustion of muscular regenerative capacity, and chronic local inflammation leading to substitution of myofibers by connective and adipose tissue. DMD patients suffer from continuous and progressive skeletal muscle damage followed by complete paralysis and death, usually by respiratory and/or cardiac failure. No cure is yet available, but several therapeutic approaches aiming at reversing the ongoing degeneration have been investigated in preclinical and clinical settings. Autophagy is an important proteolytic system of the cell and has a crucial role in the removal of proteins, aggregates, and organelles. Autophagy is constantly active in skeletal muscle and its role in tissue homeostasis is complex: at high levels, it can be detrimental and contribute to muscle wasting; at low levels, it can cause weakness and muscle degeneration, due to the unchecked accumulation of damaged proteins and organelles. The causal relationship between DMD pathogenesis and dysfunctional autophagy has been recently investigated. At molecular level, the Akt axis is one of the key dysregulated pathways, although the molecular events are not completely understood. The aim of this review is to describe and discuss the clinical relevance of the recent advances dissecting autophagy and its signaling pathway in DMD. The picture might pave the way for the development of interventions that are able to boost muscle growth and/or prevent muscle wasting.